2019
DOI: 10.1103/physrevb.99.014415
|View full text |Cite
|
Sign up to set email alerts
|

Angular-dependent spin dynamics of a triad of permalloy macrospins

Abstract: We experimentally and theoretically characterize the angular dependent microwave response of three-macrospin-vertex structures that can serve as a node in various spin ice lattices. The macrospins consist of patterned permalloy thin films with an elliptical cross-section together with an in-plane aspect ratio allowing an Ising-like behavior together with bulk modes as low-frequency excitations in the field range of interest. Various branches of the frequency-magnetic field curves display atypical behaviors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Newly emerging coherent x-ray scattering techniques [56] appear to be the best method for shedding light on these open questions. Three-nanomagnet trimers and kagome-based artificial spin ice systems also pose an intriguing case for studies on spin dynamics [31,57,58] and the dipolar trimerized triangular lattice will be an interesting addition to those investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Newly emerging coherent x-ray scattering techniques [56] appear to be the best method for shedding light on these open questions. Three-nanomagnet trimers and kagome-based artificial spin ice systems also pose an intriguing case for studies on spin dynamics [31,57,58] and the dipolar trimerized triangular lattice will be an interesting addition to those investigations.…”
Section: Discussionmentioning
confidence: 99%
“…As remarked in Refs. [24] and [25], as far as the fundamental modes are concerned, the macrospins behave largely independently of each other, and hence the full FMR spectrum can be thought of as the superposition of the single frequency curves of each single macrospin, as taken alone. In particular, in those works it was demonstrated that, when the field is applied at an angle lower than 45 • with respect to the macrospin axis, the corresponding fundamental mode dispersion is almost linear.…”
Section: Variation With the Applied Magnetic Field Anglementioning
confidence: 99%
“…When the angle is around 75 • , the curve initially (i.e., at high field values) shows a linear behavior and then (on approaching zero field) reaches a plateau. When the angle gets very close or equal to the critical value of 90 • , the frequency curve displays a W -shape behavior 24,25 .…”
Section: Variation With the Applied Magnetic Field Anglementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The magnetic response of the individual segments themselves is also of interest, and the case of permalloy ellipses has been studied via Brillouin scattering for magnetic fields along the in-plane principal axes, [5][6][7][8] and via the timeresolved magneto-optic Kerr effect (TR-MOKE). 9 We recently completed a study of the microwave response of three-fold, 120°-symmetric, clusters of such ellipses 10 and their angular dependence 11 ; our future intension is to incorporate these vertices into honeycomb or Kagome spin-ice lattices. But prior to this, it is important to characterize the behavior of the isolated elements used to assemble these structures, so as to examine the extent to which the responses of the individual ellipses govern the overall response of the clusters and, ultimately, lattices assembled from them.…”
Section: Introductionmentioning
confidence: 99%